Prospective assessment of cosmesis before and after genital surgery. Issue 1 (February 2017) - Nokoff, N.J.; Palmer, B.; Mullins, A.J.; Aston, C.E.; Austin, P.; Baskin, L.; Bernabé, K.; Chan, Y.-M.; Cheng, E.Y.; Diamond, D.A.; Fried, A.; Frimberger, D.; et al.
Summary: Introduction: Little data exist about the surgical interventions taking place for children with disorders of sex development (DSD). Most studies that have evaluated cosmetic outcomes after genitoplasty have included retrospective ratings by a physician at a single center. Objective: The present study aimed to: 1) describe frequency of sex assignment, and types of surgery performed in a cohort of patients with moderate-to-severe genital ambiguity; and 2) prospectively determine cosmesis ratings by parents and surgeons before and after genital surgery. Study design: This prospective, observational study included children aged <2 years of age, with no prior genitoplasty at the time of enrollment, moderate-to-severe genital atypia, and being treated at one of 11 children's hospitals in the United States of America (USA). Clinical information was collected, including type of surgery performed. Parents and the local pediatric urologist rated the cosmetic appearance of the child's genitalia prior to and 6 months after genitoplasty. Results: Of the 37 children meeting eligibility criteria, 20 (54%) had a 46, XX karyotype, 15 (40%) had a 46, XY karyotype, and two (5%) had sex chromosome mosaicism. The most common diagnosis overall was congenital adrenal hyperplasia (54%). Thirty-five children had surgery; 21 received feminizing genitoplasty, and 14 had masculinizing genitoplasty. Two families decided against surgery. At baseline, 22 mothers (63%), 14 fathers (48%), and 35 surgeons (100%) stated that they were dissatisfied or very dissatisfied with the appearance of the child's genitalia. Surgeons rated the appearance of the genitalia significantly worse than mothers ( P < 0.001) and fathers ( P ≤ 0.001) at baseline. At the 6-month postoperative visit, cosmesis ratings improved significantly for all groups ( P < 0.001 for all groups). Thirty-two mothers (94%), 26 fathers (92%), and 31 surgeons (88%) reported either a good outcome, or they were satisfied (see Summary Figure); there were no significant between-group differences in ratings. Discussion: This multicenter, observational study showed surgical interventions being performed at DSD centers in the USA. While parent and surgeon ratings were discordant pre-operatively, they were generally concordant postoperatively. Satisfaction with postoperative cosmesis does not necessarily equate with satisfaction with the functional outcome later in life. Conclusion: In this cohort of children with genital atypia, the majority had surgery. Parents and surgeons all rated the appearance of the genitalia unfavorably before surgery, with surgeons giving worse ratings than parents. Cosmesis ratings improved significantly after surgery, with no between-group differences. Summary Fig postoperative cosmesis ratings at baseline and 6 months.